Structural and Functional Changes in Heart Tissues of Hetero- and Homeothermic Animals Under Artificial and Natural Hypometabolism - Lomako, Viktoria V.; Shilo, Alexsandr V.; Kovalenko, Igor F. (Problems of Cryobiology and Cryomedicine, 2016)
During artificial hypometabolism (combined effect of hypoxia, hypercapnia and hypothermia) there was a decrease in temperature of body (TB) down to (17 ± 1) and (16 ± 1)°C and heart rate down to (99 ± 20) and (66 ± 16) beats/min in rats and hamsters, respectively, and under hibernation it reduced down to (8 ± 1)°C and 15–13 beats/min. The hyperemia of veins, arteries and capillaries; increased perivascular and interstitial spaces; signs of grained, hydropic and hyaline-drop dystrophies (focally),as well as numerous nuclei at various necrobiosis stages (karyopyknosis, karyorhexis and karyolysis) were herewith observed in myocardial tissue. In addition, 2 hrs later artificial hypometabolism there were revealed the blood thrombi in vessels, nuclear-free zones of necrosis, and in rats even large nuclei in some cardiomyocytes. The changes persisted even 24 hrs later, but the most of those were reversible after TB and blood circulation recovery and had an adaptive nature, but the activation of necrobiotic processes was known to be promoted the acceleration of physiological regeneration. Probl Cryobiol Cryomed 2016; 26(4): 308–321